Effectiveness of anti-mullerian hormone-tailored protocol compared to conventional protocol in women undergoing in vitro fertilization: A randomized controlled trial - Sumi Thomas; Mousumi Acharya; K Muthukumar; Achamma Chandy; Mohan S Kamath; T K Aleyamma (Wolters Kluwer Medknow Publications, 2018)
Background: Assessment of ovarian reserve before an in vitro fertilization cycle (IVF) is one among the many factors that predicts a successful cycle. Individualized protocol based on ovarian reserve is designed to optimize the pregnancy outcome without compromising the patient safety. Although authors have shown that anti-Mullerian hormone-tailored (AMH) protocols have reduced the treatment burden and improved pregnancy rates, a few others have questioned its efficacy. Aims: The aim of this study was to decide whether the AMH-tailored protocol or the conventional protocol better decides IVF outcomes. Setting and Design: Prospective randomized controlled trial conducted at a tertiary level university hospital. Materials and Methods: Patients undergoing their first IVF cycle who fulfilled the inclusion criteria were recruited and randomized to each group. Serum follicle-stimulating hormone was done for the patients on day 2 or 3 of a prior menstrual cycle, and serum AMH was done in the preceding cycle. Statistical Analysis: Analysis was performed using SPSS software version 16. Results and Conclusion: There were 100 patients in each group. A total of 83 patients underwent embryo transfer in the conventional group and 78 patients in the AMH group. The clinical pregnancy rates per initiated cycle (36.4% vs. 33.3%) and per embryo transfer (45.1% vs. 41.3%) were similar in both the groups. There was no statistical difference in the number of cycles cancelled due to poor response or the risk of ovarian hyperstimulation syndrome in both the groups. Hence, this study showed the similar effectiveness of AMH-tailored protocol and conventional protocol in women undergoing IVF.